A Analysis of the Implementation of Formative and Summative Assessment in the Learning Process of Islamic Religious Education - Siti Zaenab Raihanah; Sania Nur Kamilah; Annisa Ulfa Dila; Dudun Najmudin (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2026)
The learning process is closely related to assessment, especially through formative and summative evaluations, which play an important role in improving learning effectiveness. In the context of Islamic Religious Education, evaluation not only measures mastery of material but also the application of Islamic values in daily life. However, the reality on the ground shows that the implementation of evaluation still faces various challenges that impact the quality of learning. This study aims to analyze the implementation of formative and summative evaluations by teachers at SMP Islam Nurul Karomah Sukabumi, as well as to identify the obstacles encountered in the process. The method used is descriptive qualitative research with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the implementation of evaluation by teachers does not yet fully reflect the ideal principles of formative and summative evaluation. One of the contributing factors is the limited understanding of teachers regarding evaluation concepts, as well as the lack of professional training to support competency development. Therefore, efforts are needed to enhance teachers' capacity in understanding and applying evaluation appropriately to support continuous improvement in the learning process and outcomes of students.